Leaving the Wolf’s Glen: Measuring Decanonization in the Digital Age - Meyer, Stephen (Musica Docta, 2016)
This essay explores the idea of “decanonization” in reference to the “Wolf’s Glen Scene” (the Act II Finale) of Carl Maria von Weber’s Der Freischütz. It uses the presence of Der Freischütz excerpts in succeeding editions of the Norton Anthology of Western Music as an index of the opera’s centrality to the music-historical canon. While Weber’s opera seems to have maintained its relative position in the anthology, the very idea of music history as organized around a canon of works has been in steep decline.